The C677T mutation of the 5, 10-methylenetetrahydrofolate reductase gene is a moderate risk factor for spina bifida in Italy. Issue 12 (December 1998) - de Franchis, R; Buoninconti, A; Mandato, C; Pepe, A; Sperandeo, M P; Del Gado, R; Capra, V; Salvaggio, E; Andria, G; Mastroiacovo, P
Abstract : OBJECTIVE: To estimate the risk for spina bifida associated with the common mutation C677T of the MTHFR gene in a country with a relatively low prevalence of NTDs. DESIGN: Case-control study. SUBJECTS: Cases: 203 living patients affected with spina bifida (173 myelomeningocele and 30 lipomeningocele); controls: 583 subjects (306 young adults and 277 unselected newborns) from northern and central-southern Italy. SETTING: Cases: three spina bifida centres; young adult controls: DNA banks; newborn controls: regional neonatal screening centres. MAIN OUTCOME MEASURES: Prevalence of the C677T genotypes in cases and controls by place of birth; odds ratios for spina bifida and estimated attributable fraction. RESULTS: The prevalence of T/T, T/C, and C/C genotype was 16.6%, 53.7%, and 29.7% in controls and 25.6%, 43.8%, and 30.6% in cases, respectively. We found no differences between type of defect or place of birth. The odds ratio for spina bifida associated with the T/T genotype v C/C plus T/C was 1.73 (95% CI 1.15, 2.59) and the corresponding attributable fraction was 10.8%. No increased risk was found for heterozygous patients (OR=0.79, 95% CI 0.53-1.18). CONCLUSION: This study, as well as the meta-analysis we updated, shows that homozygosity for the MTHFR C677T mutation is a moderate risk factor in Europe, and even in Italy where there is a relatively low prevalence of spina bifida. The estimated attributable fraction associated with this risk factor explains only a small proportion of cases preventable by periconceptional folic acid supplementation. Thus, other genes involved in folate-homocysteine metabolism, their interaction, and the interaction between genetic and environmental factors should be investigated further.